Football helmet impact standards in relation to on-field impacts. (December 2017) - Sproule, David W; Campolettano, Eamon T; Rowson, Steven
Youth football helmets currently undergo the same impact testing and must satisfy the same criteria as varsity helmets, although youth football players differ from their adult counterparts in anthropometry, physiology, and impact exposure. This study aimed to relate football helmet standards testing to on-field head impact magnitudes for youth and varsity football helmets. Head impact data, filtered to include only impacts to locations in the current National Operating Committee on Standards for Athletic Equipment standard, were collected for 48 collegiate players (ages 18–23 years) and 25 youth players (ages 9–11 years) using helmet-mounted accelerometer arrays. These on-field data were compared to a series of National Operating Committee on Standards for Athletic Equipment standard drop tests with a youth and varsity Riddell Speed helmet. In the on-field data, the adult players had a higher frequency of impact than the youth players, and a significant difference in head acceleration magnitude only existed at the top location (p < 0.001). In the laboratory drop tests, the only significant difference between the youth and varsity helmets was at the 3.46 m/s (61 cm) impact to the front location (p = 0.0421). Drop tests generated head accelerations within the top 10% of measured on-field impacts, at all locations and drop heights, demonstrating that drop tests are representative of the most severe head impacts experienced by youth and adult football players on the field. Current standards have been very effective at eliminating skull fracture and severe brain injury in both populations. This analysis suggests that there is not currently a need for a youth-specific drop test standard. However, there may be such a need if helmet testing standards are updated to address concussion, paired with a better understanding of differences in concussion tolerance between youth and adult populations.